PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - Prihatin Ningsih Sagala (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2018)
The aim of this study were to improve the students’ mathematics creative thinking ability by appliying mathematic problem-based learning model on three variables linear equation system subject in X IPA 2 SMA Negeri 3 Pematangsiantar. The type of this research was a classroom action research. The subject of this study was the students of X IPA 2 SMA Negeri 3 Pematangsiantar that amounts of 30 students. The object of this study was the students’ mathematics creative thinking ability by appliying problem based learning model. This research was done in two cycles. Based on data analysis, the first cycle provided that 13 students (43,33%) from 30 students already achieved the success criteria (≥70). After the second action, it obtained that 23 students (76.67%) from 30 students already achieved the success criteria. Occur a rising classical completeness percentage in amount of 33,34%. Based on the classical criteria, this percentage already fulfilled. Based on the result of this research, it can be concluded that has occurred a rising of mathematics creative thinking ability in X IPA 2 SMA Negeri 3 Pematangsiantar so the applying of the problem-based learning could be used as one of the learning alternative to increase the mathematics creaitve thinking ability.